Dengue Outbreak during Ongoing Civil War, Taiz, Yemen - Alghazali, KhairAlah A.; Teoh, Boon-Teong; Loong, Shih-Keng; Sam, Sing-Sin; Che-Mat-Seri, Nurul-Asma-Anati; Samsudin, Nur-Izyan; Yaacob, Che-Norainon; Azizan, Noor-Syahida; Oo, Adrian; Baharudin, Nur-Adilah; Tan, Kim-Kee; Abd-Jamil, Juraina; et al. (Emerging infectious diseases, 2019)
We identified dengue in ≈51% of patients given a clinical diagnosis of suspected dengue in Taiz, Yemen, during 2016. The cosmopolitan genotype of dengue virus type 2 was most common; viruses appeared to have originated in Saudi Arabia. Damage to public health infrastructure during the ongoing civil war might enable dengue to become endemic to Yemen.